Korelasi Karakteristik Fisik Rumah dan Tingkat Kerentanan Sosio-Ekonomi di Tepian Sungai Kapuas Pontianak - Ely Nurhidayati; Trida Ridho Fariz (Department of Urban and Regional Planning, Diponegoro University, 2021)
Kampung Dalam Bugis is an area in Pontianak City located in the Kapuas River and the Landak River branch. This area is a kampung and settlement that marked the establishment of Pontianak City. Kampung Dalam Bugis Village is located on the bank of a river, impacting flood disaster vulnerability. Therefore, it is necessary to study the correlation between the physical characteristics of the house and the level of socio-economic vulnerability. This study aims to analyze the correlation between the physical characteristics of the houses and the level of socio-economic vulnerability at the riverbanks. The analysis used to assess socio-economic vulnerability is scoring from data collected from interviews and filling out questionnaires. The study used to determine the relationship between the house's physical characteristics to indicators of socio-economic vulnerability is chi-square. The assessment of the community's socio-economic vulnerability on the banks of the Kapuas River consists mostly of high vulnerability classes. Chi-square analysis shows that indicators of socio-economic vulnerability such as the head of the family's educational level have a relationship to the house's characteristics, such as the type of house and the area of the house. This initial research still needs to be developed, such as using logistic regression analysis. There is more vital evidence that the information can be used as a basis for determining or at least as a validator for indicators of socio-economic vulnerability. Physical information of the house is easier to find data through observation and even image interpretation.